Cytokine expression in peripheral blood mononuclear cells of dogs with mitral valve disease. (May 2016) - Mavropoulou, A.; Guazzetti, S.; Borghetti, P.; De Angelis, E.; Quintavalla, C.
Highlights: IL-1α, IL-1β, IL-6, IL-8, TGF-β1, TNF-α mRNA was measured in MMVD dogs and controls. Elevated IL-8 mRNA levels were detected in dogs with more advanced MMVD. Positive association between IL-8 and LVIDd, nLVIDs, E/A, E Vmax was detected. TGF-β1 mRNA was higher in the stage B2 MMVD group. No difference was found for IL-1α, IL-1β, IL-6 and TNF-α. Abstract: Inflammation plays an important role in the pathogenesis of congestive heart failure (CHF). In humans with CHF, increased production and high plasma concentrations of tumour necrosis factor-α (TNF-α), interleukin (IL)-6, IL-1, IL-8 and transforming growth factor-β (TGF-β) have been associated with disease progression and a negative prognosis. The aim of this study was to investigate whether differences in cytokine blood mRNA expression exist between clinically healthy dogs and dogs with myxomatous mitral valve disease (MMVD); to determine if the expression was related to the severity of MMVD, and to detect any correlations with echocardiographic parameters of cardiac remodelling. Twenty-three dogs with MMVD of varying severity and six clinically healthy dogs were included in the study. Whole blood samples were obtained for measurement of mRNA expression of IL-1α, IL-1β, IL-6, IL-8, TGF-β1, TNF-α by reverse transcriptase-PCR (RT-PCR). There were statistically significant differences between clinically healthy dogs and dogs with MMVD for IL-8 and TGF-β1 gene expression. IL-8 expression increased with increasing MMVD severity and TGF-β1 expression was higher in asymptomatic dogs with echocardiographic signs of cardiac remodelling (American College Veterinary Internal Medicine class B2) than in all other groups. These results could suggest the involvement of these cytokines at different stages of the disease.